Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Budaya Organisasi Dan Work Life Balance Terhadap Retensi Karyawan Ramayana Departement Store Cabang Alun-Alun Kota Malang - Juliana Anggraini; Mohammad Rizal; Sulton Sholehuddin (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study examines the influence of leadership style, work motivation, organizational culture, and work life balance on employee retention at Ramayana Department Store, Alun-Alun Branch, Malang City. Using a quantitative approach, data were collected from 68 permanent employees through a Likert scale questionnaire and analyzed using multiple linear regression. Validity, reliability, and classical assumption tests were conducted prior to hypothesis testing. The results show that leadership style, work motivation, organizational culture, and work life balance each have a positive and significant effect on employee retention. Simultaneously, all variables significantly influence employee retention. These findings highlight the importance of effective leadership, enhanced motivation, a positive organizational culture, and balanced work life policies in improving employee retention. The study provides practical implications for human resource management strategies in the retail industry. Keywords: Leadership Style, Work Motivation, Organizational Culture, Work Life Balance, Employee Retention.